Small and Medium-Sized Aneurysm Outcomes Following Intracranial Aneurysm Treatment Using the Pipeline Embolization Device: A Subgroup Analysis of the PLUS Registry - Zhang, Hongyun; Li, Li; Zhang, Hongqi; Liu, Jianmin; Song, Donglei; Zhao, Yuanli; Guan, Sheng; Maimaitili, Aisha; Wang, Yunyan; Feng, Wenfeng; Wang, Yang; Wan, Jieqing; et al. (Frontiers in Neurology, 2022)
Objective The purpose of this work was to summarize the real-world safety and efficacy of Pipeline Embolization Device (PED) therapy for small and medium-sized intracranial aneurysms in China. Methods Patients from the PED in China post-market multi-center registry study (PLUS) with aneurysms smaller than 12 mm were selected. Radiographic outcomes were assessed using digital subtraction angiography. Clinical outcomes included functional outcomes (modified Rankin Scale, MRS) in the early postoperative period ( ≤ 30 days) and early postoperative complications associated with PED therapy. Results A total of 652 patients with a combined 754 aneurysms were included in this study (mean age of 53.9 ± 10.3 years, 68.7% women). Mean aneurysm diameter was 6.78 ± 2.67 mm. Of the 687 stents deployed, 99.7% (685/689) were successfully deployed. In this study, 64.7% (488/754) of aneurysms were treated with only the PED, whereas 35.3% (266/754) were subjected to PED-assisted therapy. Radiographic outcome at the last follow-up (median time: seven months) was available for 64.3% (485/754) of the aneurysms. 82.5% (400/485) of aneurysms demonstrated complete occlusion (Raymond Roy Grade I). 81.4% (395/485) of aneurysms were found to meet the study's primary effectiveness outcome. At the early postoperative period, the mRS score was determined to be 0–2 vs. 3-6 in 98.2% (640/652) vs. 1.8% (12/652) of the cases, respectively. The combined major morbidity and mortality rate was 3.2% (21/652). Conclusion In the largest study of PED therapy for small and medium-sized intracranial aneurysms to date, pipeline-assisted coil embolization was chosen more often than multiple stent implantation for aneurysm treatment, demonstrating good results, high surgical success rates, high occlusion rates, and low morbidity and mortality. Clinical Trial Registration www.ClinicalTrials.gov, identifier: NCT03831672.